Navigating Institutional Press: The Psychological Enterprise and Self-Transcendence of Elderly in Nursing Homes: Navigasi Tekanan Institusional: Psychological Enterprise dan Aktualisasi Diri Transenden pada Lansia di Panti Jompo - Gretha Paduli; Ferdinand Kalesaran; Frangky Kandioh; Preysi Siby (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Background: The dominant discourse often positions the elderly in nursing homes as passive recipients of medical care. However, psychologically, they actively engage in Psychological Enterprise to maintain autonomy and well-being amidst institutional limitations. Objective: This study explores the psychological enterprise of the elderly in nursing homes through the integrated lens of Maslow’s self-transcendence and Murray’s psychogenic needs and press. Method: A qualitative phenomenological approach was employed. In-depth interviews were conducted with 12 elderly residents (aged 65-82) in a nursing home in Tondano, Indonesia. Data were analyzed using Braun and Clarke’s thematic analysis. Results: The findings reveal two major themes: (1) Elderly actively pursue self-transcendence (spirituality and generativity), bypassing the lower tiers of Maslow's hierarchy; (2) A constant friction exists between Murray’s psychogenic needs (affiliation, nurturance, autonomy) and negative institutional press (rigid schedules, restricted visits). To cope, the elderly develop adaptive psychological enterprises, balancing compliance with subtle assertions of independence. Conclusion: Nursing homes must shift from a purely medical-care model to a psychogenically empowering environment that accommodates the elderly's need for meaning and autonomy.